Nursing Care Plan ; Anxiety Disorders In Pregnant Women With Primigravida (Cephaloc Pelvic Dispropotion) - achmad sairul mardliyaini; Novela Eka Candra Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2022)
ABSTRACT Introduction : Cepalo Pelvic Disproportion (CPD) or photopelvic disproportion is describing a discrepancy between the size of the fetus and the size of the pelvis, a certain pelvic size is not large enough to accommodate the expulsion of the fetus through the pelvis until vaginal delivery occurs. Initially, the patient will experience CPD, which is the lack of width of the mother's pelvis in removing the baby or the baby is too large, making it difficult to expel the fetus. Relaxation therapy is very important to reduce anxiety, because anxiety in this case is related to the concern of the first pregnant woman who will have surgery. The effective non-pharmacological relaxation therapy according to the research results is Slow Deep Breathing relaxation therapy (deep breathing relaxation). This case study aims to determine Slow Deep Breathing relaxation therapy in reducing anxiety / anxiety. Research Methods : This case study uses a descriptive design with a nursing care approach. The subjects of the case study were two primigravid pregnant women with cases of Cephalo Pelvic Disproportion who experienced anxiety. Results : This case study shows that after Slow Deep Breathing relaxation therapy, anxiety has decreased with decreased worry verbalization, decreased anxiety behavior, decreased tense behavior, improved blood pressure, decreased tremor, improved sleep patterns. The results of Slow Deep Breathing relaxation therapy can reduce anxiety in primigravida pregnant women who experience anxiety. Conclusion : Looking at the results of this case study, the application of appropriate nursing care in dealing with anxiety problems in primigravida pregnant women in the case of Cephalo Pelvic Disporopotion is one of them with Slow Deep Breathing relaxation therapy. Keywords : primigravida pregnant women, anxiety, Cephalo Pelvic Disporopotion, Slow Deep Breathing relaxation therapy.